Atividade do extrato e óleo de Cymbopogon citratus sobre biofilmes de Candida albicans - ROCHA , Jessica Marques da Hora (2019)
Introduction. Cymbopogon citratus is known for its antifungal, mosquito repellent, insecticide, antidiabetic, antiseptic, anti-mutagenic, anticancer and anti-inflammatory activities. Aim. To evaluate the activity of Cymbopogon citratus extract and oil on Candida albicans’ biofilms on abiotic surfaces. Methodology. The hydroalcoholic extract of Cymbopogon citratus was prepared according to Ramos et al. (2012) with some modifications. Extraction of the essential oil was performed from fresh plant material by the hydrodistillation method, using the Clevenger system. Fragments of central venous catheter, urinary tube and needle were subjected to suspension of C.albicans at 0.5 McFarland scale, at 24 and 48 hours for biofilm formation. To evaluate the antifungal and biofilm removal activity of C. albicans we used the concentration of 500 μg of extract and 125 μg of C. citratus’ oil. Results. C. albicans formed strong intensity biofilms on the three abiotic surfaces in 48 hours in saline solution. In the antibiofilm activity, the oil and extract acted similarly on the probe and needle surface, while in central venous catheter the oil had a statistically significant inhibition compared to the extract. In the biofilm-removal activity of biofilm on abiotic surfaces, the extract acted similarly to the positive control; however, the oil did not show significant biofilm-removal action. Conclusion. Candida albicans ATCC colonized the vesical probe, central venous catheter and needle fragments, forming biofilms. C. citratus’ oil and extract showed antibiofilm activity and C. citratus’ extract was more effective in biofilm removal.